2021
DOI: 10.1177/0886260521991294
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Factors in Culpability Ratings and Rape Proclivity in Stranger and Acquaintance Rape: Validation of Rape Vignettes in a Community Sample

Abstract: Rape is a serious concern globally. Past research has identified Ambivalent Sexism (AS), Rape Myth Acceptance (RMA), and the victim–perpetrator relationship as key constructs influencing rape blame attributions and rape proclivity. Limitations with methodologies have, however, limited the practical implications of past research, particularly in the context of underpowered samples and a lack of transparency in vignette development and implementation. In the current research, three studies aimed to validate mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…A high score indicated that participants implicated the man more in the assault. As our past research indicates a less than perfect correlation between victim and perpetrator culpability (Persson & Dhingra, 2021), we suggest that there is a utility in measuring these constructs separately, rather than as one combined measure. The scale items, as well as their relation to the underlying constructs can be found in Table 1.…”
Section: The Current Reportmentioning
confidence: 70%
See 4 more Smart Citations
“…A high score indicated that participants implicated the man more in the assault. As our past research indicates a less than perfect correlation between victim and perpetrator culpability (Persson & Dhingra, 2021), we suggest that there is a utility in measuring these constructs separately, rather than as one combined measure. The scale items, as well as their relation to the underlying constructs can be found in Table 1.…”
Section: The Current Reportmentioning
confidence: 70%
“…While there is mixed evidence as to the difference between some of these constructs (e.g., Gravelin et al, 2018;Richardson & Campbell, 1980;Shaver & Drown, 1986), our recent exploratory analyses (Persson & Dhingra, 2021) indicated that women subjected to rape were attributed significantly more control, than blame, or responsibility. As such, there is an evident need for validated measures of these constructs, as this will contribute to a strengthening of the methodology of this field.…”
Section: Introduction Overviewmentioning
confidence: 78%
See 3 more Smart Citations